Identification of in vivo induced antigens of the malacosporean parasite Tetracapsuloides bryosalmonae (Cnidaria) using in vivo induced antigen technology - Kumar, Gokhlesh; Sudhagar, Arun; Shivam, Saloni; Nilsen, Frank; Bartholomew, Jerri L.; El-Matbouli, Mansour (Frontiers in Cellular and Infection Microbiology, 2022)
Tetracapsuloides bryosalmonae is a malacosporean endoparasite that causes proliferative kidney disease (PKD) in wild and farmed salmonids in Europe and North America. The life cycle of T. bryosalmonae completes between invertebrate bryozoan and vertebrate fish hosts. Inside the fish, virulence factors of T. bryosalmonae are induced during infection or interactions with host cells. T. bryosalmonae genes expressed in vivo are likely to be important in fish pathogenesis. Herein, we identify in vivo induced antigens of T. bryosalmonae during infection in brown trout (Salmo trutta) using in vivo induced antigen technology (IVIAT). Brown trout were exposed to the spores of T. bryosalmonae and were sampled at different time points. The pooled sera were first pre-adsorbed with antigens to remove false positive results. Subsequently, adsorbed sera were used to screen a T. bryosalmonae cDNA phage expression library. Immunoscreening analysis revealed 136 immunogenic T. bryosalmonae proteins induced in brown trout during parasite development. They are involved in signal transduction, transport, metabolism, ion-protein binding, protein folding, and also include hypothetical proteins, of so far unknown functions. The identified in vivo induced antigens will be useful in the understanding of T. bryosalmonae pathogenesis during infection in susceptible hosts. Some of the antigens found may have significant implications for the discovery of candidate molecules for the development of potential therapies and preventive measures against T. bryosalmonae in salmonids.